Acrylic Acid Synthesis from Lactide in a Continuous Liquid-Phase Process - Kadar, Julian; Heene-Würl, Nina; Nagengast, Jens; Kehrer, Matthias; Taccardi, Nicola; Wasserscheid, Peter; Collias, Dimitris; Dziezok, Peter; Hahn, Simon; Albert, Jakob (ACS Sustainable Chemistry & Engineering, 2019)
Synthesis of bulk chemicals from biogenic resources is gaining increasing interest in industry and academia. In the present study, we demonstrate the continuous production of acrylic acid (AA) from biogenic lactide in a liquid-phase reaction using the ionic liquid tetrabutylphosphonium bromide as reaction medium and 2-bromopropionic acid as acid catalyst precursor. We here present a ﬁrst continuous setup for AA production from LA derivatives in the liquid phase on a 10 L scale. The process operates at 200 °C and leads to AA yields of 72% in industrially relevant space−time−yields of up to 50 g/(h·L). We demonstrate continuous operation over 6 h time-on-stream, eﬃcient product isolation and successful catalyst recycling.<br
Keywords: Lactide; Liquid phase; Acrylic acid; Continuous process; Miniplant; Upscaling

Highly selective synthesis of acrylic acid from lactide in the liquid phase - Nagengast, Jens; Hahn, Simon; Taccardi, Nicola; Kehrer, Matthias; Kadar, Julian; Collias, Dimitris; Dziezok, Peter; Wasserscheid, Peter; Albert, Jakob (ChemSusChem, 2018)
A new reaction system for the highly selective, hydrobromic acid catalyzed conversion of lactide into acrylic acid under mild conditions is reported. The applied liquid reaction system consists of a temperature‐stable bromide‐containing ionic liquid and 2‐bromopropionic acid as a source of dry HBr, with no volatile organic solvent being used. This allows for the in situ removal of the formed acrylic acid, leading to an unmatched acrylic acid selectivity of over 72 % at full lactide conversion. Accounting for leftover reaction intermediates on the way to acrylic acid, which could be recycled in an elaborate continuous process, the proposed reaction system shows potential for acrylic acid yields well above 85 % in the liquid phase. This opens new avenues for the effective conversion of biogenic lactic acid (e.g., obtained by fermentation from starch) to acrylic acid. The resulting bio‐acrylic acid is a highly attractive product for, for example, the diaper industry, where we expect consumers to be especially sensitive to aspects of sustainability.

Interface of Ionic Liquids and Carbon: Ultrathin [C1C1Im][Tf2N] Films on Graphite and Graphene - Rietzler, Florian; Nagengast, Jens; Steinrück, Hans-Peter; Maier, Florian (Journal of Physical Chemistry C, 2015)
We investigated the initial adsorption behavior and growth of thin films of ionic liquid (IL) [CCIm][TfN] on highly ordered pyrolytic graphite (HOPG) and on a full and a fractional graphene layer on Ni(111). We found that the initial adsorption behavior and growth strongly depended on the underlying substrate. On HOPG, the IL forms an initial wetting layer with a coverage of 0.5 ML and anions and cations next to each other in direct contact with the substrate. On a complete graphene layer on Ni(111), the wetting layer has twice the thickness with alternately oriented ion pairs next to each other. On top of these wetting layers, further IL growth occurs in 3D islands, with the island formation being less pronounced on the graphene layer. On the fractional graphene layer on Ni(111), initial IL adsorption preferentially occurs on bare Ni surface areas, with anions on top of cations, followed by 3D island growth on both the bare and the graphene-covered surface regions.

Renewable superabsorbent polymers (bio-SAP) enabled by renewable acrylic acid (bio-AA), produced via the dehydration of lactic acid or its derivatives - Collians, Dimitris; Godlewski, Jane; Velasquez, Juan; Dziezok, Peter; Kehrer, Matthias; Nagengast, Jens; Kadar, Julian; Taccardi, Nicola; Albert, Jakob; Wasserscheid, Peter (ABSTRACTS OF PAPERS OF THE AMERICAN CHEMICAL SOCIETY, 2019)
CRIS-Team WoS Importer:2020-05-02

Zwitterionic Hydrobromic Acid Carriers for the Synthesis of 2-Bromopropionic Acid from Lactide - Kehrer, Matthias; Mehler, Julian; Taccardi, Nicola; Nagengast, Jens; Kadar, Julian; Collias, Dimitris; Dziezok, Peter; Wasserscheid, Peter; Albert, Jakob (ChemSusChem, 2018)
A convenient and highly efficient way of synthesizing 2‐bromopropionic acid (2‐BrPA) from lactide is presented. The procedure uses ionic liquids obtained from the addition of HBr to ammonium‐based zwitterions as the solvent and bromination agent. The buffered HBr acidity, high polarity, and charge stabilizing character of the ionic liquid (IL) enable the synthesis of 2‐BrPA with excellent selectivity. The best results are obtained with an imidazolium‐based IL, that is, 1‐(4‐butanesulfonic acid)‐3‐methylimidazolium bromide ([MIMBS]Br). The HBr loading and water content of the IL are crucial parameters for the bromination reaction. The formed 2‐BrPA product can be selectively isolated by extraction from the IL, and the unconverted substrate remains in the [MIMBS]Br IL for the next run. Successful recycling of the IL over four cycles is demonstrated.
Keywords: bromination; ionic liquids; lactide; renewable resources; zwitterions